Creativity as capital in the literacy classroom : Youth as multimodal design - Walsh, Christopher S. (Literacy, The United Kingdom Literacy AssociationLiteracy, The United Kingdom Literacy Association, 2007)
Many school literacy practices ignore adolescents' new digitally mediated subjectivity as it has been shaped by the new media age. Youth possess often unappreciated repertories of practice which allow them to use their imagination and creativity to combine print, visual and digital modes in combinations that can be applied to new educational, civic, media and workplace contexts. This paper reports on research in two middle years classrooms in New York City's Chinatown, where students' design skills were recognised and validated when they were encouraged to critically re-represent curricular knowledge through multimodal design. The curriculum, rather than privileging print-only representations, recognised the linguistic, social, economic and cultural capital that different students brought to school. The findings suggest schools should harness youths' creativity – that often manifests itself through their capital resources – as they integrate and adapt to the new digital affordances acquired through their out-of-school literacy practices.
Keywords: création; literacy; multimodalité